Функціональна модель інформаційної системи прогнозування результату інфаркту міокарда - Якубовська, С. В. (ХНУРЭ, 2017)
The given work is devoted to the functional model of the information system for predicting the outcome of myocardial infarction is proposed, based on author's methods for predicting the development of postmyocardial infarction syndrome and recurrent myocardial infarction. The constructed functional model provides a detailed representation of the process of functioning of the information system, and also allows to realize the process of predicting the outcome of myocardial infarction.
Keywords: інфаркт міокарду; кардіологія